Average urinary flow rate and its association with handgrip strength. (4th December 2020) - Chiu, Hao-Tse; Kao, Tung-Wei; Peng, Tao-Chun; Chen, Yuan-Yuei; Chen, Wei-Liang
Abstract: Background: Voiding dysfunction became a difficult problem for the elderly because of the underactive bladder (UAB). It was considered that the degeneration of detrusor muscle was the main etiology. In recent years, more articles focus on relationship between UAB and decreased muscle strength. Besides, handgrip strength (HGS) is an early indicator to detect frailty and muscle weakness in systemic reviews. Method: Our study involved 2258 males from NHANES datasets (2011–2012, who were divided into quartiles by urine flow rate (UFR), which was measured by uroflowmetry. Multivariate regression models were performed to analyze the associations between UFR and HGS. Results: The UFR had a positive correlation to the HGS by multivariate regression models in males (β coefficient: 1.348, 95% confidence interval (CI): 0.530, 2.166, p = 0.001). The male participants with the highest quartile of UFR have a greater HGS than those with lowest quartile of UFR (β coefficient: 4.546, 95% CI: 2.462, 6.630, p < 0.001). Higher UFR was associated with lower odds of low HGS (OR: 0.489, 95% CI: 0.350, 0.684, p < 0.001) in the fully-adjusted model. Conclusions: Our research highlighted that the UFR had a strong associated with the HGS in the healthy group.